Localization of Social Distancing Norm to Combat Covid -19 Pandemic in Indonesia - Herningtyas, Ratih (Technium Social Sciences Journal, 2024)
The purpose of this research is to explore the localization of social distancing norm in Indonesia during the Covid-19 pandemic. The Covid-19 pandemic has spread globally, affecting many aspects of human life. WHO, as a world health authority, encourages the implementation of social distancing norm to prevent the spread of Covid-19. However, countries around the world use various strategies to implement social distancing, such as lockdowns or social restrictions. Using Finnemore and Sikkink’s norm life cycle and Amithav Acharya’s norm localization, this article finds that the internalization and localization of social distancing norm in Indonesia are carried out through four efforts: determining the Covid-19 pandemic as a national disaster, forming a task force for the acceleration of Covid-19 countermeasures, and establishing social restriction policies through the Large-Scale Social Restrictions (PSBB) and the Enforcement of Restrictions on Community Activities (PPKM) policies and socializing new habits such as maintaining distance and using masks. The localization of the social distancing norm is influenced by the domestic situation and the local norm of helping each other which is implemented through various movements such as jaga tangga, 3N1, canthelan, etc.